Neurobiogical and biochemical mechanisms of the influence of alcohol on the central nervous system and cognitive personal activity - Vovk Viktoriya; Strashok Oleg (Psychiatry, Neurology and Medical Psychology, 2022)
Topicality. The problem of alcohol addiction remains an acute medical and social problem. The intense stressful biochemical background of today greatly burdens alcohol abuse with all the consequences that follow. Given the availability of alcohol in our country, the negative multi-organ effects, including on the nervous and mental systems and cognitive functions, as well as the attractiveness of its rapid anxiolytic, hypnotic and other effects, the problem of alcohol addiction requires close attention of specialists.The purpose of this work was to determine the neurobiological and biochemical mechanisms of the formation of cognitive disorders due to alcohol consumption.Materials and methods: Modern scientific publications on neurobiological and biochemical mechanisms of the effect of ethanol on the central nervous system and, as a result, on human cognitive activity were analyzed.Results: The analysis of literature data showed that with alcohol addiction, the frontal lobes of the cerebral hemispheres are more prone to damage, which is manifested by a violation of executive functions (ability to abstract and plan, inhibition of perseverative processes, switching between different cognitive processes, speed of cognitive processes, etc.). The neurotransmitter systems of the brain are also negatively affected. The disease progresses as the compensatory capabilities of the body are exhausted, the role of which is performed by the increased synthesis of catecholamines in the central nervous system. Hypotheses explaining the phenomenology of the neuropsychological defect in alcoholism are considered.Conclusions: Thus, timely detection of brain dysfunctions associated with alcohol dependence in patients is of great importance at all stages of work - both in diagnostic and therapeutic processes. Also, theses from the given analytical data can be used when conducting psychoeducation as a stage of CBT intervention in alcohol addiction for all participants of the therapeutic process.